Lifestyle and Risk Factors in Hemorrhoidal Disease - De Marco, Stefania; Tiso, Domenico (Frontiers in Surgery, 2021)
Constipation, a low fiber diet, a high Body Mass Index, pregnancy, and a sedentary lifestyle are often assumed to increase the risk of hemorrhoidal disease (HD). However, evidence regarding these factors is controversial. This mini-review aims to examine and critically analyze the association between main risk factors and the prevalence of HD, focusing both on the patient's clinical history and on a tailored treatment. Moreover, some practical suggestions about lifestyle and conservative approaches are given to help clinicians in the management of patients with HD and to obtain the best results from therapy.